"Work is Love Made Visible": Purpose and Community in Clubhouses - Laura Yakas (Disability Studies Quarterly, 2017)
What does work mean to people socially defined by their inability to work? This article explores "work" in Psychosocial Clubhouses, strengths-based programs for people experiencing psychiatric disability, where members – not clients or patients – work at operating their clubhouse alongside staff. I draw upon three years of experience in a Michigan clubhouse, as a volunteer, social work intern, and ethnographer. I explore the meaning of work – defined as "purposeful activity that builds community," challenging the narrow neoliberal definition of work as "paid employment" – from the perspective of clubhouse members. In the clubhouse, "dis-ability" becomes a misnomer, as members demonstrate remarkable "ability" within the clubhouse's work environment. Interestingly, this work environment demands close, authentic relationships between members and staff, which dismantle conventional hierarchies between professionals and clients in mental health programs. In this work environment, members come to feel needed and valued, countering common feelings associated with psychiatric disability such as dependence and a lack of self-efficacy. Through developing a sense of purpose and community – arguably human needs – many members are able to live self-defined meaningful lives, in spite of their marginalized social position.
Keywords: work; purpose; community; belonging; psychiatric disability; psychiatric rehabilitation; Clubhouse Model; neoliberal-ableism